The Russian Arctic vision: implications for Arctic governance in the context of climate change - Lansetti, Sandi (Università Ca' Foscari Venezia, 2018)
The thesis is focused on the Russian Arctic and the implications that climate change would have on its governance. Three main “extensive” uses for the Russian Arctic are analyzed: offshore fossil fuel extraction, security and militarization and sea transportation. It is very likely that oil and gas extraction will be the driver of Russian Arctic policy and investments in the near future, however, the dedicated chapter suggests that a consistent part of those resources would probably not be extracted. Security and militarization will be challenged by the declining sea ice and the increasing accessibility of the Arctic Ocean and the human activities there, but they would not dominate the Artic agenda like for instance during the Cold War. Sea transportation will be developed beside oil and gas extraction projects for the export of Russian natural resources to the world markets. The Russian Arctic vision is mainly shaped by these Arctic uses. A critical discourse analysis of its official documents and strategy for the Arctic point out the importance of oil and gas and the Northern Sea Route development, while climate change mitigation and adaptation are mainly a declaration of intents rather than a concrete objective with its action plan. The Russian government still sees climate change as an opportunity to develop its northern territories, while at the same time it is recognizing the threats it represents for the country. Russia is the world's biggest energy exporter and its climate policy is dependent on this. The Russian Arctic vision has not progressed to the point yet to consider other premises of security and governance needs that will become more and more important due to the melting sea ice and the rapidly changing Arctic.